ChemInform Abstract: Spiroalkaloids and Coumarins from the Stem Bark of Pauridiantha callicarpoides. Issue 3 (January 2015) - Tatuedom, Ostend K.; Kouam, Simeon F.; Yapna, Diane Beatrice; Ngadjui, Bonaventure T.; Green, Ivan R.; Choudhary, M. Iqbal; Lantovololona, Jeanne E. R.; Spiteller, Michael
Abstract isolation and structure elucidation of a new spiroalkaloid, 7‐epi‐javaniside (I), along with seven known compounds